2020
DOI: 10.31234/osf.io/2kp7x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating and comparing behavioural and electrophysiological estimates of neural health in cochlear implant users

Abstract: 1Variations in neural health along the cochlea can degrade the spectral and temporal 2 representation of sounds conveyed by cochlear implants (CIs) . We evaluated and compared 3 several methods that have been proposed as estimates of neural health patterns, in order to 4 explore the extent to which the different measures provide converging and consistent neural 5 health estimates. All measures were obtained from the same 11 users of the Cochlear 6 Corporation CI. The two behavioural measures were multipulse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 1 publication
4
15
0
Order By: Relevance
“…Our paradigm seems more promising in measuring the charge integration properties of the SGNs at MCL than at detection threshold. This contrasts with most proposed psychophysical predictors of neural health that generally focus on the across-electrode variation in the effects of parameters such as inter-phase gap, pulse rate, and stimulus polarity, at detection threshold (Bierer and Faulkner 2010;Pfingst et al 2015;Carlyon et al 2018;Goehring et al 2019;Jahn and Arenberg 2019a, b;Brochier et al 2020;Mesnildrey et al 2020). Although there might indeed be more across-electrode variability at threshold (because of stimulating more targeted populations of neurons), it is worth nothing that some of these measures correlate between threshold and MCL (e.g.…”
Section: Further Research Directionsmentioning
confidence: 93%
“…Our paradigm seems more promising in measuring the charge integration properties of the SGNs at MCL than at detection threshold. This contrasts with most proposed psychophysical predictors of neural health that generally focus on the across-electrode variation in the effects of parameters such as inter-phase gap, pulse rate, and stimulus polarity, at detection threshold (Bierer and Faulkner 2010;Pfingst et al 2015;Carlyon et al 2018;Goehring et al 2019;Jahn and Arenberg 2019a, b;Brochier et al 2020;Mesnildrey et al 2020). Although there might indeed be more across-electrode variability at threshold (because of stimulating more targeted populations of neurons), it is worth nothing that some of these measures correlate between threshold and MCL (e.g.…”
Section: Further Research Directionsmentioning
confidence: 93%
“…The use of different measures and criteria between studies to select electrode channels for deactivation could have led to the mixed results. Furthermore, it is likely that different measures of electrode-nerve distance and presumed neural health along the cochlea interact and influence the spread of excitation in a complex manner so that the optimal selection of electrodes for improving speech-in-noise performance is not obvious (Brochier et al 2020). Generally, all of the site-selection studies each used only a single measure to guide the selection of deactivated channels without taking into account all the aspects of electrode-nerve distance, local neural health and their interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that focussed thresholds are not the only measure believed to be affected by neural health (Pfingst, et al, 2015). A recent study (Brochier, et al, 2020) obtained several such measures, including the effect of IPG on ECAPs and the effects of pulse rate and stimulus polarity of behavioral thresholds. They found that none of these measures correlated with each other, and used a biophysical model (Joshi, et al, 2017) The lack of correlation between the two could therefore be due to inaccuracies in either estimate.…”
Section: Discussionmentioning
confidence: 99%